KerjaKarya: An Inclusive Digital Solution to Expand Access for the Disabled Labour Force - Mohaimin, Susetiyo; Aditya, Addin (Journal of Artificial Intelligence and Software Engineering, 2025)
People with disabilities often face significant challenges in accessing the world of work due to limited inclusive information media and the stigma of low productivity. To address these issues, this research aims to develop and test the KerjaKarya application, a web-based platform specifically designed to facilitate people with disabilities, especially the physically, hearing, and speech impaired, in finding job vacancies, submitting applications, and building communities. This research uses the System Development Life Cycle (SDLC) method with a waterfall approach, involving data collection from literature studies, interviews with people with disabilities, and testing using black box techniques and user trials. The trial involved five job applicants, four companies, and one customer service with a Likert scale-based questionnaire instrument. The results showed that the application successfully met the needs of users with a friendly interface and relevant features, such as registration, application submission, and vacancy management. The implication of this research is that it provides a practical solution to improve accessibility and participation of people with disabilities in an inclusive labour market. This research also opens up opportunities for further development, such as the integration of artificial intelligence and skills training services